SOCIAL PROTECTION SYSTEM OF THE POPULATION IN THE CONDITIONS OF A TRANSFORMATIONAL ECONOMY - M. Sh. Rakhimova (GREEN ECONOMY AND DEVELOPMENT, 2026)
This paper presents a scholarly examination of the evolutionary transformation of the concept of social protection, its theoretical underpinnings, and its contemporary development. The research explores the shift of the social protection system from conventional approaches to a more digitalized and integrated framework, along with an analysis of its regional features and efficiency. Furthermore, in the context of global economic changes, the study highlights the expansion of the social protection system and its influence on socio-economic stability